Mechanical and vibration isolation behaviour of acrylonitrile-butadiene rubber/multi-walled carbon nanotube composite machine mounts. (26th November 2017) - Tsongas, Konstantinos; Tzetzis, Dimitrios; Mansour, Gabriel
ABSTRACT: An effective analytical-experimental test method is used in the current work to characterize the vibration isolation performance of nitrile-butadiene rubber (NBR) reinforced with multi-walled carbon nanotubes (MWCNTs). A series of specimens were manufactured with 10 different NBR/MWCNTs concentrations (0 to 20wt% MWCNTs). In order to determine the static compression stiffness and hysteresis of the mounts, compression and cyclic tests were conducted. The vibration isolation properties were determined through the analysis of the transmissibility of a suitably designed test system. NBR's mechanical properties and vibration isolation properties were improved with the addition MWCNTs, suggesting that the enhancement of NBR with MWCNTs was rather effective. Considering the obtained results, the dynamic stiffness of NBR and its capacity to isolate vibration can be adjusted by controlling the proportion of MWCNTs.